Review of root canal irrigant delivery techniques and devices - Yeon-Jee Yoo; Su-Jeong Shin; Seung-Ho Baek (Korean Academy of Conservative Dentistry, 2011)
Introduction Eliminating the residual debris and bacteria in the root canal system is one of the main purposes of the endodontic treatment. However, the complexity on the anatomy of the root canal system makes it difficult to eliminate the bacterial biofilm existing along the root canal surface and necrotic pulp tissue by mechanical instrumentation and chemical irrigation. Recently, more effective irrigant delivery systems for root canal irrigation have been developed. The purpose of this review was to present an overview of root canal irrigant delivery techniques and devices available in endodontics. Review The contents of this paper include as follows; - syringe-needle irrigation, manual dynamic irrigation, brushes - sonic and ultrasonic irrigation, passive ultrasonic irrigation, rotary brush, RinsEndo, EndoVac, Laser Conclusion Though technological advances during the last decade have brought to fruition new agitation devices that rely on various mechanisms, there are few evidence based study to correlate the clinical efficacy of these devices with improved outcomes except syringe irrigation with needle and ultrasonic irrigation. The clinicians should try their best efforts to deliver antimicrobial and tissue solvent solutions in predictable volumes safely to working length.